1970
DOI: 10.3329/ijns.v1i1.8608
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Morphometrical studies on Semi lunar Heart valves of Indigenous Cattle (<i>Bos indicus</i>)

Abstract: Twenty heart specimens of healthy indigenous cattle (Bos indicus) of different age group (04 groups) in Sylhet District were collected for gross morphology and morphometrical analysis of cusps or leaflets and papillary muscles to study the measurement of the lengt h of the free margin of the cusps of the aortic and pulmonary valves and anatomical assessment for future bioprosthetic purpose for heterografting in the cardiac valvular human patients. It was found that the pulmonary valves consisted of three semil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Significant amounts of the RCO positioned above the IL have been reported in humans(Engel et al., 1975; Nasr & El Tahlawi, 2018). However, in animals, there were few reports of this disposition(Akhtar et al., 1970; Durán et al., 2007). According to the comparative analysis shown in Figures 2 and 3, it was observed that only the RCO was above the IL in the analysed specimens (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Significant amounts of the RCO positioned above the IL have been reported in humans(Engel et al., 1975; Nasr & El Tahlawi, 2018). However, in animals, there were few reports of this disposition(Akhtar et al., 1970; Durán et al., 2007). According to the comparative analysis shown in Figures 2 and 3, it was observed that only the RCO was above the IL in the analysed specimens (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…When CO are located above IL, perfusion of the coronary arteries occurs unimpeded. This type of arrangement has been observed with various levels of frequency in humans (Cavalcanti et al, 2003;Engel et al, 1975), but in animals (Akhtar et al, 1970;Barszcz et al, 2020;Durán et al, 2007) reports of such dispositions are rare. Records of CO above IL in humans and mice have supported the theory that, when in development, arterial vessels arise distally at the level of the sinotubular junction (Spicer et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…El hueso cardíaco es ampliamente conocido en rumiantes domésticos, como bovinos, caprinos y ovinos, además de haber sido reportado también en dromedarios (14,15). Además, hay informes de ese hueso también en chimpancés, aunque estos animales no son rumiantes (16).…”
Section: Discussionunclassified